MONTE CARLO-BASED INVESTIGATION OF MICRODOSIMETRIC DISTRIBUTION OF HIGH ENERGY BRACHYTHERAPY SOURCES. Issue 1 (5th June 2019) - Chattaraj, Arghya; Selvam, T Palani; Datta, D
Abstract: FLUKA-based Monte Carlo calculations were carried out to study microdosimetric distributions in air and in water for encapsulated high energy brachytherapy sources ( 60 Co, 137 Cs, 192 Ir and 169 Yb) by simulating a Tissue Equivalent Proportional Counter (Model LET1/2) having sensitive diameter of 1. 27 cm for a site size of 1 μm. The study also included microdosimetric distributions of bare sources. When the sources are in air, for a given source, the source geometry does not affect the y ¯ F and y ¯ D values significantly. When the encapsulated 192 Ir, 137 Cs and 60 Co sources are in water, y ¯ F and y ¯ D values increase with distance in water which is due to degradation in the energy of photons. Using the calculated values of y ¯ D, relative biological effectiveness (RBE) was obtained for the investigated sources. When 60 Co, 137 Cs and 192 Ir sources are in water, RBE increases from 1.03 ± 0.01 to 1.17 ± 0.01, 1.24 ± 0.01 to 1.46 ± 0.02 and 1.50 ± 0.01 to 1.75 ± 0.03, respectively, when the distance was increased from 3–15 cm, whereas for 169 Yb, RBE is about 2, independent of distance in water.